1986
DOI: 10.1051/jphys:019860047080132100
|View full text |Cite
|
Sign up to set email alerts
|

Two-wave mixing in sodium vapour

Abstract: We have observed a unidirectional oscillation in a ring cavity when a sodium atomic vapour interacts with a non resonant pump beam. We have checked that the frequency of the oscillating beam is almost the same as the frequency of the pump beam. We propose a theoretical interpretation of the origin of a two-wave mixing process in an atomic vapour. We show the necessity of a relaxation process and we emphasize the close relationship between this effect and the Bloembergen PIER 4 resonances

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
7

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 28 publications
0
7
0
7
Order By: Relevance
“…This central structure corresponds to a two-wave mixing resonance [24] and its shape and width give indications on the response times of the dynamical modes of the molasses that are excited by the probe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This central structure corresponds to a two-wave mixing resonance [24] and its shape and width give indications on the response times of the dynamical modes of the molasses that are excited by the probe.…”
Section: Discussionmentioning
confidence: 99%
“…connected to the two-wave mixing resonances (also called stimulated Rayleigh or two-beam coupling resonances) that have been observed in atomic vapors [24,25,21]. These resonances are generally associated with the excitation of a slow atomic observable by the combined effect of a pump beam and a probe beam.…”
Section: E Rayleigh Resonances L Adiabatic Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The output power observed in this measurement arises from one-photon-gain-based laser oscillation [9], as is seen from the fact that the maximum output power occurs for A f ^ -O//, corresponding to the peak of driven-atom one-photon gain. In addition, we have found that the laser threshold behavior is consistent with that expected for one-photon laser oscillation.…”
mentioning
confidence: 96%
“…1(a), and degenerate twophoton gain occurs at (o d -~ ft///2. Since this frequency is removed from spectral regions of strong one-photon gain [9], it is possible to selectively enhance two-photon gain using a high-finesse optical cavity. Note that the periodic structure of the dressed-atom energy spectrum guarantees relatively strong, near resonantly enhanced, degenerate two-photon transitions.…”
mentioning
confidence: 99%